INFLAMMATORY MARKERS IN CHRONIC DIABETIC COMPLICATIONS: A LITERATURE REVIEW - Thaina De Santos Silva, Larissa; Paula De Sousa Figueiredo, Maria (Health and Society, 2023)
Diabetes Mellitus (DM) is a chronic disease that has been questioned the most because it has become a public health issue worldwide. The state of inflammation may have had an origin in the inflammatory diet, a lack of exercise or other factors associated with Diabetes Mellitus (DM). This work aims to carry out a systematic literature review evaluating the effect of inflammation on chronic complications of Diabetes Mellitus. The study is a bibliographical research, consisting of books and scientific articles. A literature review on the subject will be carried out through scientific academic journals and articles, through databases such as Scielo, Periodicals and Google Scholar, in order to compare the different information found on these platforms, addressing the treatment of Diabetes Mellitus. Articles were searched using the following descriptors: Inflammatory Markers, Diabetes Mellitus, Inflammation, Epidemiology of Diabetes Mellitus. 20 articles were searched, of which 40% addressed the epidemiology of DM, 25% addressed the main inflammatory markers.